APPLICATION OF LOW-FIELD NUCLEAR MAGNETIC RESONANCE AND PROTON MAGNETIC RESONANCE IMAGING IN EVALUATION OF ‘JINXIU’ YELLOW PEACH’S STORAGE SUITABILITY - ZHOU, Hui-juan; YE, Zheng-wen; YU, Zhi-fang; SU, Ming-shen; DU, Ji-hong (Emirates Journal of Food and Agriculture, 2017)
In this study, changes in the transverse relaxation time (T2), signal intensity (A2), and images of ‘Jinxiu’ yellow peach fruits were investigated using low-field nuclear magnetic resonance (LF-NMR) and proton magnetic resonance imaging (1H-MRI). The water content, (determined using centrifuging technology), fruit firmness, and ethylene production were evaluated at 4±1°C and 25±2°C. The results showed a signal peak (A2) and T2 at 500–1000 ms. On days 4–6, T2 changed from 796 ms to 861 ms, and decreased with longer time at 25°C. Water content also decreased and high adjusted determination coefficient (adj-R2) values with water content were found for T2 (R2 = 0.95) and A2 (R2 = 0.99), indicating a high degree of fit for the prediction equations. A2 decreased and T2 shortened after prolonged storage at 4°C and high adj-R2 values were found between the water content and T2 (R2 = 0.93) and A2 (R2 = 0.97).Ethylene production and firmness were the same as for T2, A2, and internal breakdown at 25°C for 4–6 days, and 4°C for 16–21 days. Compared with storage at 25°C, low temperature storage inhibited water loss and also prohibited internal breakdown. T2 and A2 can be used to evaluate the storage characteristics of yellow peach fruits, and the internal breakdown of pulp tissue could be clearly observed by 1H-MRI, which is a function of LF-NMR. 1H-MRI can provide high-resolution images showing the internal structure of intact peaches. Thus, LF-NMR is a new technology that could be an effective and simpler method for monitoring and predicting water content, as well as detecting quality issues during peaches storage.